2023
DOI: 10.3390/healthcare11192623
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and Minimal Important Change of the Arabic Disabilities of the Arm, Shoulder and Hand (DASH) in Patients with Upper Extremity Musculoskeletal Disorders

Ali H. Alnahdi

Abstract: The aim of this study was to examine the responsiveness of the Arabic Disabilities of the Arm, Shoulder and Hand (DASH) and to quantify its minimal important change (MIC) for improvement. People with upper extremity musculoskeletal problems who were receiving physical therapy were evaluated at baseline and again during a follow-up appointment, with a median time frame of 7 days between the two testing sessions (range of 6 to 72 days). The participants completed the Arabic DASH, Global Assessment of Function (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Many research comparing the efficacy of different treatments have been sparked by the controversy about which one is better. [6][7][8][9][10][11][12][13][14] In our study the mean age of patients was 50.08+6.43yrs. Crawshaw PD 14 reported mean age was 56 (range 40-78), Hajivandi S et al 15 , reported mean age of 52.37 ± 6.61, and Siraj M et al 16 reported 49 ±9.3 years of mean age in patients with chronic shoulder pain.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Many research comparing the efficacy of different treatments have been sparked by the controversy about which one is better. [6][7][8][9][10][11][12][13][14] In our study the mean age of patients was 50.08+6.43yrs. Crawshaw PD 14 reported mean age was 56 (range 40-78), Hajivandi S et al 15 , reported mean age of 52.37 ± 6.61, and Siraj M et al 16 reported 49 ±9.3 years of mean age in patients with chronic shoulder pain.…”
Section: Discussionmentioning
confidence: 48%
“…The DASH score ranges from 0 to 100, with a higher score indicating the worst function and symptoms. 13 The VAS is a 100-mm ratings with of 0 to 4 mm can be considered no pain; 5 to 44 mm, mild pain; 45 to 74 mm, moderate pain; and 75 to 100 mm, severe pain. 13 Every patient in the study had an intra-articular corticosteroid injection, in which administration of a combination consisting of one milliliter (of 2% lignocaine) and two milliliters (of 80 mg) of methylprednisolone using a single syringe was done.…”
Section: Methodsmentioning
confidence: 99%